Delineation of Subregions in the Early Postnatal Human Cerebellum for Design-Based Stereologic Studies - Anna Fichtl; Andreas Büttner; Patrick R. Hof; Christoph Schmitz; Maren C. Kiessling (Frontiers in Neuroanatomy, 2018)
Recent design-based stereologic studies have shown that the early postnatal (<1 year of age) human cerebellum is characterized by very high plasticity and may thus be very sensitive to external and internal influences during the first year of life. A potential weakness of these studies is that they were not separately performed on functionally relevant subregions of the cerebellum, as was the case in a few design-based stereologic studies on the adult human cerebellum. The aim of the present study was to assess whether it is possible to identify unequivocally the primary, superior posterior, horizontal, ansoparamedian, and posterolateral fissures in the early postnatal human cerebellum, based on which functionally relevant subregions could be delineated. This was tested in 20 human post mortem cerebellar halves from subjects aged between 1 day and 11 months by means of a combined macroscopic and microscopic approach. We found that the superior posterior, horizontal, and posterolateral fissures can be reliably identified on all of the specimens. However, reliable and reproducible identification of the primary and ansoparamedian fissures was not possible. Accordingly, it appears feasible to perform subregion-specific investigations in the early postnatal human cerebellum when the identification of subregions is restricted to crus I (bordered by the superior posterior and horizontal fissures) and the flocculus (bordered by the posterolateral fissure). As such, it is recommended to define the entire cerebellar cortex as the region of interest in design-based stereologic studies on the early postnatal human cerebellum to guarantee reproducibility of results.